The Effect of Hidden Objective in the Concept-mapping & Coaching Method on Explaining Skills of Prospective Teachers - Kartikowati, Rr Sri; Gimin, Gimin; Nas, Syakdanur (Dinamika Pendidikan, 2018)
This study aims to analyze the effect of hidden objectives in the Introduction to Management lectures that use the Concept-mapping and Coaching method on explaining skills of prospective teacher students. This research is included in the development study. The study population was all students of introduction to management (non-Microteaching) in the Faculty of Teacher Training which consisted of two classes (PE-A 40 students as control class and PE-B 39 students as experimental class). This study used simple random sampling technique to determine 14 sample people from each class. Primary data were obtained from samples of two classes through observation in explaining skills, and then data were analyzed descriptively and in in analysis of Independent sample t-test. From the descriptive analysis, the average score of explaining skills of prospective teacher students in the experimental class was higher than the control class score. The results of the analysis of the t-test for equality test showed that there are convincing differences in explaining skills in prospective teacher students between the control class and the experimental class. Thus, the hidden objective in the Concept-mapping & Coaching Method in the lecture of Introduction Management can improve the better explaining skills of prospective student teachers. Suggestions from the results of this study are that other non-Microteaching lecturers in the Faculty of Teacher Training will use hidden objectives to accelerate mastery of student teacher teaching skills in an effort to support the realization of professional prospective teachers.